Biomass straw and multi-component composite modification preparation method thereof
Through the composite modification technology of enzyme-degenerative starch and malate esterified modified bamboo powder, the problems of brittle cracking of starch straws and poor mechanical properties of bamboo powder composite materials were solved, and a low-price, high-strength and high-strength composite material were prepared. Biomass straws solve the problems of poor performance and high cost of existing biodegradable straws, and achieve high performance and long life of straws.
Patent Information
- Application Number
- CN202411271786.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-09-11
AI Technical Summary
The existing degradable straws have problems such as poor service performance, high cost and difficulty in mass production. Especially the starch straws are prone to brittle cracks and are prone to swelling and rupture in hot drinks, which seriously restricts its large-scale production application, and the combination of bamboo powder and starch The material has poor mechanical properties and is difficult to replace traditional plastic straws.
Through the composite modification technology of enzyme-degenerative starch and malic acid esterified modified bamboo powder, the starch is modified by the composite enzyme method, and the bamboo powder is crosslinked and esterified modified by malic acid to prepare a low-priced , high strength and toughness of biomass straw.
The prepared biomass straw has high toughness, is not easy to deform, has a long storage time, is stable at high temperature, and is resistant to chemical corrosion, which significantly improves the mechanical properties and hydrophobic properties of the straw, extends the service life and reduces the failure caused by material deterioration. or security issues.
Smart Images

Figure CN119161642A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of modified composite materials, and in particular relates to a biomass straw and a multi-component composite modification preparation method thereof. Background Art
[0002] Non-degradable plastic straws are considered to be hazardous waste due to their small size, light weight, and difficulty in recycling. Food and catering industries across the country are actively seeking to use degradable straws to replace traditional plastic straws. At present, there are mainly two types of straws on the market: paper straws and polylactic acid (PLA) straws. Paper straws have poor service performance and are easily softened and rotten in hot drinks; although the service performance of PLA straws is close to that of traditional plastic straws, in terms of raw material cost, PLA straws (about 0.05 yuan / strand) are much higher than plastic straws (about 0.01 yuan / strand) and paper straws (about 0.03 yuan / strand), which limits their application. In addition, other degradable straws on the market have problems such as poor service performance, high cost, and difficulty in mass production, such as bamboo straws (not durable, easy to crack, easy to mold, limited resources, complex processing, need to be hand washed and manually polished, etc.), glass straws (fragile, difficult to store, high price, etc.), metal straws (difficult to clean, metallic taste, etc.), wheat straws (weak, easy to break, etc.), etc. Therefore, developing a degradable straw with low production cost, good product performance, easy to completely degrade, and able to completely replace traditional plastic straws is the primary task that urgently needs to be solved at home and abroad.
[0003] As a natural polymer compound, starch has the advantages of a wide range of raw materials, many varieties, high yield, low price, and complete degradation in the natural environment (the products are CO2 and H2O), and has broad market development prospects. In particular, starch is widely favored by the food packaging industry because of its green, safe and edible nature. However, although there are starch straw products on the market, almost all of them have problems such as easy brittle cracking of the straws, easy swelling and rupture in hot drinks, and dissolution of flocs, which seriously restricts the large-scale production and application of starch straws. Modified starch is based on the inherent properties of natural starch. In order to improve the performance of starch and expand its application range, physical, chemical or enzymatic treatment is used to introduce new functional groups on the starch molecules or change the size of starch molecules and the properties of starch particles, thereby changing the natural properties of starch and making it more suitable for certain application requirements. After the original starch is modified, the molecular arrangement is increased in an orderly and tight manner, which will significantly improve the mechanical, barrier and hydrophobic properties of starch straws.
[0005] As a natural polymer material, bamboo powder has the advantages of low price, high strength, low density, good mechanical properties, and complete biodegradability. However, bamboo powder is rich in cellulose, hemicellulose, lignin and other substances, which makes it difficult for bamboo powder and starch to be compatible. The mechanical properties of the composite material are poor, such as low strength, easy to break, difficult to bend, and no toughness. Therefore, there are few existing technologies that use bamboo powder and starch to prepare biomass straws. Summary of the invention
[0006] The purpose of the present invention is to provide a biomass straw and a multi-component composite modification preparation method thereof in order to solve the above problems.
[0007] The present invention achieves the above-mentioned purpose through the following technical solutions:
[0008] A biomass straw and a multi-component composite modification preparation method thereof, characterized in that it comprises the following steps:
[0009] S1. Preparation of enzyme-modified starch:
[0010] S101, mixing plant starch with phosphate buffer, gelatinizing with boiling water and adjusting to a suitable temperature;
[0011] S102, performing enzymatic hydrolysis on the mixture;
[0012] S103, performing enzyme inactivation operation after enzymatic hydrolysis, and then performing aging and retrogradation treatment, washing with water, centrifuging and drying to obtain enzyme-modified starch;
[0013] S2. Preparation of malic acid esterified modified bamboo powder:
[0014] S201, mixing bamboo powder with sulfuric acid solution in a certain proportion, and after the reaction is completed, terminating the acid hydrolysis reaction with deionized water and removing the sulfuric acid;
[0015] S202, dialyzing with deionized water to obtain a suspension with a neutral pH, and concentrating the suspension to adjust the pH of the concentrate;
[0016] S203, mixing a certain proportion of malic acid into the concentrated solution, and performing a malic acid esterification reaction at a certain temperature;
[0017] S204, drying at 45°C, grinding, and sieving to obtain malic acid esterified modified bamboo powder;
[0018] S3. Preparation of biomass straws:
[0019] S301, mixing enzyme-modified starch and malic acid esterified modified bamboo powder to obtain a mixture A, wherein the enzyme-modified starch accounts for 30%-70%, adding a composite plasticizer to mix, and then putting it into a ziplock bag to equilibrate at room temperature and then extruding;
[0020] S302, the balanced mixture is extruded by an extrusion device, and cooled and dried.
[0021] Furthermore, in step S101, the plant starch is corn starch, the volume of the phosphate buffer is 100 mL, and the boiling water gelatinization time is 1 h.
[0022] Furthermore, in step S102, the specific steps are:
[0023] The gelatinized mixture was placed in a 50°C water bath, stabilized for 10 minutes, and 4U / g α-amylase (based on dry starch) was added and reacted for 30 minutes. After inactivating the enzyme in a boiling water bath for 20 minutes, 500U / g branching enzyme (based on dry starch) was added after cooling to 65°C and reacted for 20 minutes. After inactivating the enzyme in a boiling water bath for 20 minutes, the mixture was placed in a 47°C water bath, and 40U / g pullulanase (based on dry starch) was added and reacted for 24 hours.
[0024] Furthermore, in step S103, the specific steps are: inactivate the enzyme in the mixture by boiling water for 20 minutes, place it at 4°C for aging for 24 hours, wash the starch with water and centrifuge it, wash the starch with anhydrous ethanol, and dry it after centrifugation to obtain enzyme-modified starch.
[0025] Further, in step S201, the concentration of the sulfuric acid solution is 60%, the ratio of the bamboo powder to the sulfuric acid solution is 1:5, the unit is w / v, the reaction time is 50 minutes, the deionized water is 15 times the product, and a high-speed centrifuge is used to remove sulfuric acid through water exchange / centrifugal circulation.
[0026] Further, in step S202, the specific steps are: dialyzing the suspension with deionized water to obtain a suspension with a neutral pH, concentrating the suspension to a concentration of 8% using a rotary evaporator, and then adjusting the pH of the concentrate to 3-4 using 0.1 mol / L hydrochloric acid.
[0027] Further, in step S203, the ratio of the concentrate to malic acid is 3:1, the unit is w / w, the mixing time is 10 minutes, the reaction temperature is 140° C., and the reaction time is 1 hour.
[0028] Further, in step S301, the composite plasticizer accounts for 20% of mixture A, and the composite plasticizer is a mixture of 5 parts of water, 3 parts of glycerol and 2 parts of erythritol.
[0029] Further, in step S302, the extrusion equipment is a three-screw extruder, and the extrusion temperature is divided into three temperature control zones from the extrusion outlet to the extrusion inlet: the temperature of zone 1 is 90° C., the temperature of zone 2 is 95° C., and the temperature of zone 3 is 85° C. The sample is extruded from the die head, cooled at room temperature for 48 hours, and then the straw is dried at 40° C. to a moisture content of 7.0%.
[0030] As a further optimization scheme of the present invention, the present invention also provides a biomass straw, which is prepared according to the above-mentioned biomass straw and the multi-component composite modification preparation method thereof.
[0031] The beneficial effects of the present invention are as follows: the present invention utilizes a composite enzyme method to modify the molecular structure of starch, utilizes green organic acid malic acid to perform cross-linking esterification modification on bamboo powder, and composites the enzyme-modified starch and acid-modified bamboo powder to prepare a biomass straw with low price, high strength, high toughness, and complete natural degradation. The straw has high toughness, is not prone to deformation and deterioration, and has a long storage time, reducing failures or safety problems caused by material deterioration. The straw is more stable at high temperatures, is not prone to deformation, and can better resist corrosion from chemical substances. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 A flow chart for preparing the biomass straw of the present invention;
[0033] Figure 2 This is an appearance diagram of the biomass straw of the present invention;
[0034] Figure 3 XRD diagram of the biomass straw of the present invention (a.70:30; b.60:40; c.50:50; d.40:60; e.30:70);
[0035] Figure 4 XRD patterns of aging of enzyme-modified starch / acid-modified bamboo powder composite straws with different ratios after being placed at room temperature for 30 days (a.70:30; b.60:40; c.50:50; d.40:60; e.30:70). DETAILED DESCRIPTION
[0036] The present application is further described in detail below in conjunction with the accompanying drawings. It is necessary to point out here that the following specific implementation methods are only used to further illustrate the present application and cannot be understood as limiting the scope of protection of the present application. Technical personnel in this field can make some non-essential improvements and adjustments to the present application based on the above application content.
[0037] A biomass straw and a multi-component composite modification preparation method thereof, using corn starch as raw material, firstly using α-amylase, branching enzyme and pullulanase to enzymatically hydrolyze the starch in sequence to prepare enzyme-modified starch with orderly and tight molecular arrangement, significantly improving the crack resistance and hydrophobicity of the starch; secondly, using natural organic acid L-malic acid to esterify bamboo powder to improve the viscoelasticity and toughness of the bamboo powder. The specific steps of the use include:
[0038] Weigh a certain amount of corn starch, add 100mL phosphate buffer, mix thoroughly and gelatinize in a boiling water bath for 1h, cool to room temperature, place in a 50℃ water bath, stabilize for 10min, add 4U / g α-amylase (based on starch dry basis), and react for 30min. After inactivating the enzyme in a boiling water bath for 20min, cool to 65℃ and then add branching enzyme (500U / g, based on starch dry basis) to react for 20min. After inactivating the enzyme in a boiling water bath for 20min, place in a 47℃ water bath, add 40U / g pullulanase (based on starch dry basis), react for 24h, inactivate the enzyme in a boiling water bath for 20min, place at 4℃ for aging and regeneration for 24h. Wash the starch with anhydrous ethanol after water washing and centrifugation, and dry it after centrifugation to obtain enzyme-modified starch;
[0039] Weigh a certain amount of bamboo powder, add it to 60% sulfuric acid solution in a ratio of 1:5 (w / v), stir and mix, and stir and react at room temperature for 50 minutes. After the reaction is completed, pour the product into 15 times deionized water to terminate the acidolysis reaction. Use a high-speed centrifuge to remove sulfuric acid through water exchange / centrifugal circulation, and then dialyze the suspension with deionized water to obtain a suspension with a neutral pH. Use a rotary evaporator to concentrate the suspension to a concentration of 8%, then adjust the pH of the concentrate to 3-4 with 0.1mol / L hydrochloric acid, then add malic acid in a ratio of 3:1 (w / w), stir and mix for 10 minutes, and place it in an oil bath at 140℃ and heat for 1h. After the reaction is completed, take it out, wash it with distilled water several times to remove excess unreacted malic acid, and then put the filter cake into an oven at 45℃ to dry it, grind it into powder with a mortar, sieve it, and obtain malic acid esterified modified bamboo powder.
[0040] Example 1
[0041] The enzyme-modified starch and malic acid-esterified modified bamboo powder were mixed and stirred at a constant speed in a blender for 15 minutes in a ratio of (70:30, w / w) and a composite plasticizer (20%, based on the dry basis of the main material), wherein the plasticizer was a mixture of water: glycerol: erythritol (4:4:2, w / w / w);
[0042] After the mixture is fully mixed, it is placed in a ziplock bag and extruded after balancing at room temperature (25°C, RH = 53%) for 24 hours. A three-screw extruder is used, and the extrusion temperature is divided into three temperature control zones from the extrusion outlet to the extrusion inlet: the temperature of zone 1 is 85°C, the temperature of zone 2 is 90°C, and the temperature of zone 3 is 90°C;
[0043] The sample was extruded from the die, cooled at room temperature for 24 h, and then the straw was dried at 35°C to a constant moisture content (7.0%).
[0044] Example 2
[0045] The enzyme-modified starch and malic acid-esterified modified bamboo powder were mixed and stirred at a constant speed in a blender for 15 minutes in a ratio of (60:40, w / w) and a composite plasticizer (20%, based on the dry basis of the main material), wherein the plasticizer was a mixture of water: glycerol: erythritol (6:3:1, w / w / w);
[0046] After the mixture is fully mixed, it is placed in a ziplock bag and extruded after balancing at room temperature (25°C, RH = 53%) for 24 hours. A three-screw extruder is used, and the extrusion temperature is divided into three temperature control zones from the extrusion outlet to the extrusion inlet: the temperature of zone 1 is 95°C, the temperature of zone 2 is 100°C, and the temperature of zone 3 is 95°C;
[0047] The sample was extruded from the die, cooled at room temperature for 36 h, and then the straw was dried at 40°C to a constant moisture content (7%).
[0048] Example 3
[0049] The enzyme-modified starch and malic acid-esterified modified bamboo powder were mixed and stirred at a constant speed in a blender for 15 minutes in a ratio of (50:50, w / w) and a composite plasticizer (20%, based on the dry basis of the main material), wherein the plasticizer was a mixture of water: glycerol: erythritol (5:3:2, w / w / w);
[0050] After the mixture is fully mixed, it is placed in a ziplock bag and extruded after balancing at room temperature (25°C, RH = 53%) for 24 hours. A three-screw extruder is used, and the extrusion temperature is divided into three temperature control zones from the extrusion outlet to the extrusion inlet: the temperature of zone 1 is 90°C, the temperature of zone 2 is 95°C, and the temperature of zone 3 is 85°C;
[0051] The sample was extruded from the die, cooled at room temperature for 48 h, and then the straw was dried at 40°C to a constant moisture content (7.0%).
[0052] Example 4
[0053] The enzyme-modified starch and malic acid-esterified modified bamboo powder were mixed and stirred at a constant speed in a blender at a ratio of (40:60, w / w) and a composite plasticizer (20%, based on the dry basis of the main material) for 15 minutes, wherein the plasticizer was a mixture of water: glycerol: erythritol (4:2:4, w / w / w);
[0054] After the mixture is fully mixed, it is placed in a ziplock bag and extruded after balancing at room temperature (25°C, RH = 53%) for 24 hours. A three-screw extruder is used, and the extrusion temperature is divided into three temperature control zones from the extrusion outlet to the extrusion inlet: the temperature of zone 1 is 95°C, the temperature of zone 2 is 105°C, and the temperature of zone 3 is 95°C;
[0055] The sample was extruded from the die, cooled at room temperature for 48 h, and then the straw was dried at 50° C. to a constant moisture content (7.0%).
[0056] Example 5
[0057] The enzyme-modified starch and malic acid-esterified modified bamboo powder were mixed and stirred at a constant speed in a blender for 15 minutes in a ratio of (30:70, w / w) and a composite plasticizer (20%, based on the dry basis of the main material), wherein the plasticizer was a mixture of water: glycerol: erythritol (4:3:3, w / w / w);
[0058] After the mixture is fully mixed, it is placed in a ziplock bag and extruded after balancing at room temperature (25°C, RH = 53%) for 24 hours. A three-screw extruder is used, and the extrusion temperature is divided into three temperature control zones from the extrusion outlet to the extrusion inlet: the temperature of zone 1 is 80°C, the temperature of zone 2 is 90°C, and the temperature of zone 3 is 85°C;
[0059] The sample was extruded from the die, cooled at room temperature for 36 h, and then the straw was dried at 40°C to a constant moisture content (7.0%).
[0060] Extract the straw samples prepared in Examples 1-5 ( Figure 2 Upper left picture) for performance testing:
[0061] Test 1
[0062] Soak the five groups of samples in 70℃ hot water for 30 minutes and record their appearance after soaking. Figure 2 As shown in the upper right figure, it can be seen that straw C, i.e., the straw prepared in Example 3, has the smallest degree of swelling upon water absorption, indicating that the straw does not expand significantly when in contact with liquid and can maintain its original structure and shape, which helps to prevent the straw from deforming or losing function during use, thereby providing a more stable user experience. Furthermore, it is not prone to deformation and deterioration during long-term use, thereby extending the service life of the straw and reducing the need for frequent replacement.
[0063] Test 2
[0064] The bending test was carried out on five groups of samples respectively. The test results are as follows: Figure 2As shown in the figure below, it can be seen that straw c has the largest curvature, which means that the straw prepared in Example 3 is softer and can better adapt to different containers and usage angles, providing greater flexibility in use. In some cases, a larger curvature can increase comfort during use, especially for beverage containers that require a larger bending angle.
[0065] Test 3
[0066] X-ray diffraction experiments were carried out on five groups of samples. The test results are as follows: Figure 3 As shown, it can be seen that the diffraction intensity of straw c is the largest. Samples with large diffraction intensity usually have higher crystallinity. High crystallinity materials usually have better compressive and tensile strength, are more stable at high temperatures, are not easy to deform, and are more resistant to corrosion by chemical substances, which helps the material maintain a stable shape and size during processing.
[0067] Test 4
[0068] The five groups of samples were placed at room temperature for 30 days and then subjected to X-ray diffraction experiments. The experimental results are as follows: Figure 4 As shown, it can be seen that the diffraction intensity of straw c has the smallest change amplitude, indicating that the straw prepared in Example 3 maintains structural stability during long-term storage, which is beneficial to the long-term storage of the straw and reduces failure or safety problems caused by material deterioration.
[0069] Test 5
[0070] Five groups of samples were placed in a room temperature environment, and the elastic index of 30% deformation in the diameter direction was recorded on different days. The recorded results are shown in Table 1:
[0071]
[0072] According to the results in Table 1, the elastic index of the deformation of the straw c has the smallest change range, which means that the straw prepared in Example 3 can maintain relatively stable elastic properties after a deformation of 30%, indicating that the material has high stability and reliability.
[0073] According to the above test results, it can be seen that the biomass straw prepared in Example 3 has better performance, strong toughness, is not easy to deform, has higher stability, and has the longest storage time.
[0074] The above tests all adopt existing test methods. No further improvement is made to the test methods in this application, so the detailed test process is not recorded.
[0075] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A method for preparing a multi-component composite modification of a biomass straw, characterized in that: The following steps are involved: S1. Preparation of enzyme-modified starch: S101, mixing plant starch with phosphate buffer, gelatinizing with boiling water and adjusting to a suitable temperature; S102, performing enzymatic hydrolysis on the mixture; S103, performing enzyme inactivation operation after enzymatic hydrolysis, and then performing aging and retrogradation treatment, washing with water, centrifuging and drying to obtain enzyme-modified starch; S2, malic acid esterified modified bamboo powder: S201, mixing bamboo powder with sulfuric acid solution in a certain proportion, and after the reaction is completed, terminating the acid hydrolysis reaction with deionized water and removing the sulfuric acid; S202, dialyzing with deionized water to obtain a suspension with a neutral pH, and concentrating the suspension to adjust the pH of the concentrate; S203, mixing a certain proportion of malic acid into the concentrated solution, and performing a malic acid esterification reaction at a certain temperature; S204, drying at 45°C, grinding, and sieving to obtain malic acid esterified modified bamboo powder; S3. Preparation of biomass straws: S301, mixing enzyme-modified starch and malic acid esterified modified bamboo powder to obtain a mixture A, wherein the enzyme-modified starch accounts for 30%-70%, adding a composite plasticizer to mix, and then putting it into a ziplock bag to equilibrate at room temperature and then extruding; S302, the balanced mixture is extruded by an extrusion device, and cooled and dried.
2. The method for preparing a multi-component composite modification of a biomass straw according to claim 1, characterized in that: In step S101, the plant starch is corn starch, the volume of the phosphate buffer is 100 mL, and the boiling water gelatinization time is 1 h.
3. The method for preparing a biomass straw by multi-component composite modification according to claim 2, characterized in that: In step S102, the specific steps are: The gelatinized mixture was placed in a 50°C water bath, stabilized for 10 minutes, 4U / g α-amylase was added, reacted for 30 minutes, the enzyme was inactivated in a boiling water bath for 20 minutes, cooled to 65°C, 500U / g branching enzyme was added and reacted for 20 minutes, the enzyme was inactivated in a boiling water bath for 20 minutes, placed in a 47°C water bath, 40U / g pullulanase was added and reacted for 24 hours.
4. The method for preparing a biomass straw by multi-component composite modification according to claim 3, characterized in that: In step S103, the specific steps are: inactivate the enzyme in the mixture by boiling water for 20 minutes, place it at 4°C for aging for 24 hours, wash the starch with water and centrifuge it, wash the starch with anhydrous ethanol, and dry it after centrifugation to obtain enzyme-modified starch.
5. The method for preparing a biomass straw by multi-component composite modification according to claim 4, characterized in that: In step S201, the concentration of the sulfuric acid solution is 60%, the ratio of the bamboo powder to the sulfuric acid solution is 1:5, the unit is w / v, the reaction time is 50 minutes, the deionized water is 15 times the product, and a high-speed centrifuge is used to remove sulfuric acid through water exchange / centrifugal circulation.
6. The method for preparing a biomass straw by multi-component composite modification according to claim 5, characterized in that: In step S202, the specific steps are: dialyzing the suspension with deionized water to obtain a suspension with a neutral pH, concentrating the suspension to a concentration of 8% using a rotary evaporator, and then adjusting the pH of the concentrate to 3-4 using 0.1 mol / L hydrochloric acid.
7. The method for preparing a biomass straw by multi-component composite modification according to claim 6, characterized in that: In step S203, the ratio of the concentrate to malic acid is 3:1, the unit is w / w, the mixing time is 10 minutes, the reaction temperature is 140° C., and the reaction time is 1 hour.
8. The method for preparing a multi-component composite modification of a biomass straw according to claim 7, characterized in that: In step S301, the composite plasticizer accounts for 20% of mixture A, and the composite plasticizer is a mixture of 5 parts of water, 3 parts of glycerol and 2 parts of erythritol.
9. The method for preparing a biomass straw by multi-component composite modification according to claim 8, characterized in that: In step S302, the extrusion equipment is a three-screw extruder, and the extrusion temperature is divided into three temperature control zones from the extrusion outlet to the extrusion inlet: the temperature of zone 1 is 90°C, the temperature of zone 2 is 95°C, and the temperature of zone 3 is 85°C. The sample is extruded from the die head, cooled at room temperature for 48 hours, and then the straw is dried at 40°C to a moisture content of 7.0%.
10. A biomass straw, characterized in that: A biomass straw and a multi-component composite modification preparation method thereof according to any one of claims 1 to 9 are prepared.
Citation Information
Patent Citations
Preparation method of autoclaved fly-ash bricks
CN107352935A
Bamboo powder full biodegradable material and preparation method thereof
CN110343397A
Degradable straw and preparation method
CN112662191A
Multi-element full-degradable plant-based thermoplastic esterified bio-based component
CN113321940A
Method for preparing starch-based suction pipe through cooperation of bio-enzyme and extrusion shearing
CN116766546A
